Análisis de comparación de una píldora a base de fibra soluble, una píldora de sello por alta filtración y una píldora Losseal para minimizar el daño durante la perforación de una formación naturalmente fracturada (2021)
This document explains the different characteristics of soluble fiber pills, high filtration seal pill and Losseal pill in order to make a comparative analysis to determine which of these 3 is more suitable to use as a drilling mud additive for sealing in naturally fractured formations. The cost, time and risk variables will be evaluated.